Insulin and the kidneys: a contemporary view on the molecular basis - Daza-Arnedo, Rodrigo; Rico-Fontalvo, Jorge; Aroca-Martínez, Gustavo; Rodríguez-Yanez, Tomás; Martínez-Ávila, María Cristina; Almanza-Hurtado, Amilkar; Cardona-Blanco, María; Henao-Velásquez, Carlos; Fernández-Franco, Jorge; Unigarro-Palacios, Mario; Osorio-Restrepo, Carolina; Uparella-Gulfo, Isabella (Frontiers in Nephrology, 2023)
Insulin is a hormone composed of 51 amino acids, structurally organized as a hexamer composed of three heterodimers. Insulin is the central hormone involved in the control of glucose and lipid metabolism, aiding in processes such as body homeostasis and cell growth. Insulin is synthesized as a large pre-prohormone having a leader sequence or signal peptide that appears to be responsible for transport to the endoplasmic reticulum membranes. The interaction of insulin with the kidney is a dynamic and multicenter process as it acts in multiple sites throughout the nephron. Insulin acts from the glomerulus to the renal tubule by modulating different functions such as glomerular filtration, gluconeogenesis, natriuresis, glucose uptake, regulation of ion transport, prevention of apoptosis, among others. On the other hand, the insulin receptor has shown sufficient evidence of its renal function and its responsibility for regulation of glucose homeostasis, thereby enabling us to understand the contribution in the insulin resistance phenomenon and its association with the progression of diabetic kidney disease.